Economic evaluation. Part 2: frameworks for combining costs and benefits in health care. - McIntosh, E; Luengo-Fernandez, R (2006)
In this two-part series on the economic evaluation of different health interventions, the methods for measuring costs and valuing benefits have been outlined and the methods by which the costs and benefits are collated within an economic evaluation framework have been described. Economic evaluation should be seen as a decision-making framework that renders the costs and benefits of any intervention or service explicit. In doing so, informed decisions can be made about the allocation of resources to various programmes. The outcome or benefit measure chosen will decide the actual 'type' of economic evaluation carried out. If a number of outcome measures are chosen, a variety of economic evaluations may be performed and the results used as an aid to decision making. By ensuring that the opportunity costs of programmes are minimised, this should ensure the maximisation of well-being to society given limited resources.